Fuzzy fractional Gardner and Cahn–Hilliard equations with the Atangana–Baleanu operator - Shah, Manzoor Ali; Yasmin, Humaira; Ghani, Fazal; Abdullah, Saleem; Khan, Imran; Shah, Rasool (Frontiers in Physics, 2023)
This article is devoted to investigating or computing the solutions to fuzzy fractional order Cahn-Hilliard and Gardner equations. Specifically, the fuzzy Gardner and Cahn-Hilliard equation is hybridized into two equations using hybrid techniques and the notion of a parametric fuzzy number. A combination of the novel iterative approach and the Shehu transformation is utilized for this inquiry. The procedures for computing a series of solutions to the fractional order Cahn-Hilliard and Gardner problem are provided. In addition to providing precision, simplicity, and efficacy, the applied techniques have also outperformed other current technologies. Finally, some examples are solved in order to justify our theoretical solution.